Effects of the Mitochondrial and Nuclear Genomes on Nonshivering Thermogenesis in a Wild Derived Rodent. (18th July 2018) - Bize, Pierre; Lowe, Imogen; Lehto Hürlimann, Mikko; Heckel, Gerald
Abstract: A key adaptation of mammals to their environment is their ability to maintain a constant high body temperature, even at rest, under a wide range of ambient temperatures. In cold climates, this is achieved by an adaptive production of endogenous heat, known as nonshivering thermogenesis (NST), in the brown adipose tissue (BAT). This organ, unique to mammals, contains a very high density of mitochondria, and BAT correct functioning relies on the correct functioning of its mitochondria. Mitochondria enclose proteins encoded both in the maternally inherited mitochondrial genome and in the biparentally inherited nuclear genome, and one overlooked hypothesis is that both genomes and their interaction may shape NST. By housing under standardized conditions wild-derived common voles ( Microtus arvalis ) from two distinct evolutionary lineages (Western [W] and Central [C]), we show that W voles had greater NST than C voles. By introgressing those two lineages over at least nine generations, we then experimentally tested the influence of the nuclear and mitochondrial genomes on NST and related phenotypic traits. We found that between-lineage variation in NST and BAT size were significantly influenced by the mitochondrial and nuclear genomes, respectively, with the W mitochondrial genotype being associated with higher NST and the W nuclear genotype with a larger BAT. There were significant mito–nuclear interactions on whole animal body weight and resting metabolic rate (RMR). Hybrid voles were lighter and had higher RMR. Overall, our findings turn new light on the influence of the mitochondrial and nuclear genomes on thermogenesis and building adaptation to the environment in mammals.